CONSTRAINT-INDUCED MOVEMENT THERAPY FOR LOWER EXTREMITY BALANCE AND FUNCTION IN POST-STROKE PATIENTS: A LITERATURE REVIEW - Muhamad Elfitra Salam; Nurul Aini; Nisa Hanifah; Zakir Burhan (Prodi Fisioterapi, Fikes, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Background: Constraint-induced movement therapy (CIMT) has demonstrated effective as a neurorehabilitation intervention for addressing